2020
DOI: 10.22323/2.19010206
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: gender implications for the design of outcomes, evaluation and assessment of science communication programs

Abstract: As science communication programs grow worldwide, effective evaluation and assessment metrics lag. While there is no consensus on evaluation protocols specifically for science communication training, there is agreement on elements of effective training: listening, empathy, and knowing your audience — core tenets of improvisation. We designed an evaluation protocol, tested over three years, based on validated and newly developed scales for an improvisation-based communication training at the Alan Alda Center fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Of the 29 scientists and educators, 25 (86%) identified as women. This trend in participation is in line with similar improvisation‐based science communication training programs (O'Connell et al, 2020 ). O'Connell et al ( 2020 ) assert that experiences of gender bias in communicating science influence women's communication choices.…”
Section: Description Of the Scbcsupporting
confidence: 83%
See 1 more Smart Citation
“…Of the 29 scientists and educators, 25 (86%) identified as women. This trend in participation is in line with similar improvisation‐based science communication training programs (O'Connell et al, 2020 ). O'Connell et al ( 2020 ) assert that experiences of gender bias in communicating science influence women's communication choices.…”
Section: Description Of the Scbcsupporting
confidence: 83%
“…This trend in participation is in line with similar improvisation‐based science communication training programs (O'Connell et al, 2020 ). O'Connell et al ( 2020 ) assert that experiences of gender bias in communicating science influence women's communication choices. Such experiences may have influenced the choice to participate in SCBC, for example.…”
Section: Description Of the Scbcsupporting
confidence: 83%
“…Sample sizes of participants in the articles ranged from 10 to 113 ( M = 34.9, SD = 31.74), with a median sample size of 22 participants per reported program. All 10 articles included STEM graduate students in the sample population of participants, with three studies also including post-docs, faculty, and/or other professionals (Fogg-Rogers et al, 2017; Greer et al, 2018; O’Connell et al, 2020). The majority of articles did not report participant demographics for age or ethnicity, with the exception of Fogg-Rogers et al (2017), who reported that 90% of participants were between the ages of 25 and 40, 10% of participants were between the ages 41 and 60, and two participants were of ethnically minority background, as well as Rodgers et al (2018), who reported that 16 participants were nonnative English speakers.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these studies used paired-samples t -tests to compare pretraining and posttraining scores (Akin et al, 2021; Ponzio et al, 2018; Rodgers et al, 2018; Webb et al, 2012). Two studies used mean/median comparisons for pre and post measurements of skill (O’Connell et al, 2020) and post-only measurements of self-assessed skill compared to external-assessed skill (Rubega et al, 2020 Part 1). Fogg-Rogers et al (2017) used a Wilcoxon signed-rank statistical test to compare pre and post scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation